2023
DOI: 10.1002/jmv.29058
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoviruses A and C elicit long‐lasting antibody responses with limited cross‐neutralization

Yury A. Bochkov,
Mark Devries,
Kaitlin Tetreault
et al.

Abstract: Rhinoviruses (RVs) can cause severe wheezing illnesses in young children and patients with asthma. Vaccine development has been hampered by the multitude of RV types with little information about cross‐neutralization. We previously showed that neutralizing antibody (nAb) responses to RV‐C are detected twofold to threefold more often than those to RV‐A throughout childhood. Based on those findings, we hypothesized that RV‐C infections are more likely to induce either cross‐neutralizing or longer‐lasting antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Instead, there was a turnover of the most prevalent types, which was likely influenced by temporal type dynamics. The disappearance of types after predominance at broad geographical scales was consistent with the development of long-term type-specific immunity 45 , 46 . A58 was identified as a frequent type in both the countrywide study (year 2014) and the subsequent HDSS study (year 2015/16), the recurring A58 viruses belonged to a different phylogenetic cluster.…”
Section: Discussionsupporting
confidence: 70%
“…Instead, there was a turnover of the most prevalent types, which was likely influenced by temporal type dynamics. The disappearance of types after predominance at broad geographical scales was consistent with the development of long-term type-specific immunity 45 , 46 . A58 was identified as a frequent type in both the countrywide study (year 2014) and the subsequent HDSS study (year 2015/16), the recurring A58 viruses belonged to a different phylogenetic cluster.…”
Section: Discussionsupporting
confidence: 70%
“…We found statistical association of some clusters with the year of detection which might indicate a possible relationship with the long-term immunity interference. While this clustering does not necessarily define antigenic and serotypic relatedness, it did cluster together RV-A12, RV-20, and RV-A78 which have previously shown cross-neutralizing protection [35].…”
Section: Discussionmentioning
confidence: 75%
“…However, this study emphasizes the importance of investigating correlations between genotypes and serotypes to understand longterm immunity and cross-protection. Recent research by Bochkov et al revealed crossprotection among some genetically similar genotypes in RV-A and RV-C species [35]. This fact was originally mentioned in 1982 when Cooney et al demonstrated cross-protection between 50 RV types, categorized them into 16 antigenic groups [36].…”
Section: Discussionmentioning
confidence: 96%
“…Despite the considerable sequence diversity of RV-C C-loops, we observed evidence of putative cross-reactivity at these sites bases on similar reactivity patterns between homologous C loops sequences. A recent study reported reciprocal cross-reactive neutralization between RV C2 and C40 in both mouse and human samples (Bochkov et al 2023). Our findings also grouped together RV C2 and C47 C-loops as putative cross-reactive epitopes indicating that potential cross-reactivity patterns can be deconvoluted from antibody binding profiles collected from peptide microarrays.…”
Section: Discussionmentioning
confidence: 99%